Dragon kingdom of Wrenly. Book 8, The Shattered Shore - Quinn, Jordan (Quinn, Jordan. Dragon Kingdom of Wrenly, 2022)
Ruskin, Cinder, Groth, and Roke travel to the Shattered Shore to honor Villinelle, and while there, the four dragons make discoveries that will help in the upcoming battle.